High temperature proton exchange membrane using inorganic membrane - Chan, Rumin. (2012)
In this report, a novel proton exchange membrane using a simple and cost effective gel-casting technique was fabricated. Phosphotungstic acid (HPW) was utilized as proton donator and meso-porous silica MCM-41 used as supported material was prepared and studied for application in direct methanol fuel cells at high temperatures. The highly ordered meso-porous silica was fabricated and HPW was introduced into the nanochannels of meso-silica matrix by vacuum assisted impregnation method. The as-assembled HPW/meso-silica powders were characterized by small-angle X-ray scattering (SAXS), thermogravimetric analysis TGA and derivative thermogravimetry (DTG). The fabricated composite HPW/meso-silica membranes were characterized using Autolab FRA, TGA and FESEM techniques. The effects of HPW loading and solid state loading on the microstructure, water/methanol weight gain ratio, swelling ratio, conductivity of the HPW/MCM-41 membranes are studied in detail.